The causes and effects of occupational stress in the contruction industry - A qualitative analysis of the impact work demands and pressures have on employee stress levels - Arrman, Nathalie; Björk, Emma (My University, 2017)
Occupational stress has become a major issue of the modern world, and is one of the most common work-related health problems in Europe. It has become a growing concern in many industries, not to mention the construction industry. As the construction industry is known to be challenging and highly competitive, it is important to ensure that personnel have the ability to perform at its best. Work-related stress has been identified as a major factor that impacts the success of an organization, as it negatively affects the organization’s productivity and efficiency, which in turn is costly to the company. Besides this, it is also believed to be a large contributor to reduced work satisfaction and increased absenteeism. Considering that most individuals spend a significant amount of time at work, their behavioural-, physiological- and psychological health are playing an important role both to the organization and the employees themselves. Nevertheless, managing work-related stress is a complex and challenging task for organizations. One difficulty in understanding how pressures and occupational stress impacts the personnel within the construction industry is the scarcity of empirical research in the area. Due to the importance of people management and the well-being of construction personnel for the success of an organization, this study aims to investigate the main causes and effects of occupational stress. A case study of a well-known construction company in Sweden is conducted, in order to get a better understanding of the perceptions of construction personnel. The thesis is based on a mixed methodology, with the combination of a qualitative and quantitative research approach. The study involves both face-to-face semi-structured, in depth interviews as well as an online staff survey, in order to acquire reliable, in-depth responses as well as to receive a higher response rate that could reflect the current situation. The main findings of this study were that construction personnel suffer from a high level occupational stress, particularly those who work on site. There are many various work-related risk factors within this industry, and the factors that were recognized as the most problematic are (i) amount of work, (ii) amount of overwork, (iii) not enough experienced personnel and (iiii) lack of organizational support. However, lack of control over one’s work was identified as being the factor that caused most employees’ distress, especially for construction professionals who work on sites and need to deal with unexpected events on a frequent basis. The work-life balance is low, especially among the personnel working on site, and many of them have suffered from negative consequences as a direct result of their jobs. The major issue seems to be the insufficient recovery among construction employees. There are no strategies that are sufficient and adequate enough at the time, and this calls for a change. It is necessary to create and implement workable strategies that can reduce the occupational stress levels and increase the level of employee satisfaction and retention. For those strategies to be successful, they cannot focus on an individual’s behaviour in isolation, instead more efforts should focus on the organizational environment and the industry as a whole. Especially as it has been recognized that the stress levels and well-being of construction personnel have not improved, rather retrograded.
Keywords: Samhällsbyggnadsteknik; Civil Engineering